2019
DOI: 10.28982/josam.536426
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum irisin levels in patients with endometrial hyperplasia: A controlled cross-sectional study

Abstract: Aim: Irisin, which is proteolytically splited form of fibronectin type III domain containing 5 (FNDC5), is a protein with 112 amino acid. Irisin is an exercise-induced hormone excreted primarily by cardiac muscle and skeletal cells which can be described as an exercise hormone and a new potential target for the treatment of metabolic diseases and obesity. Our goal was to evaluate the serum irisin levels in patients with endometrial hyperplasia (EH). Methods: An observational study is planned. The study populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…One-third of outpatient visits to the gynecology and obstetrics outpatient clinic and more than 70% of the patients are AUB [8]. It is seen that OCD increases with age and is effective in the transformation of age into a risky condition, especially endometrial cancer [3,6,8,12]. In the study by Şahin et al, in order to compare the endometrial thickness and histopathological results measured by transvaginal ultrasonography in premenopausal patients with abnormal uterine bleeding, it was observed that the mean age of women was 40 years and above, and they were in the premenopausal period [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One-third of outpatient visits to the gynecology and obstetrics outpatient clinic and more than 70% of the patients are AUB [8]. It is seen that OCD increases with age and is effective in the transformation of age into a risky condition, especially endometrial cancer [3,6,8,12]. In the study by Şahin et al, in order to compare the endometrial thickness and histopathological results measured by transvaginal ultrasonography in premenopausal patients with abnormal uterine bleeding, it was observed that the mean age of women was 40 years and above, and they were in the premenopausal period [6].…”
Section: Discussionmentioning
confidence: 99%
“…It is seen that OCD increases with age and is effective in the transformation of age into a risky condition, especially endometrial cancer [3,6,8,12]. In the study by Şahin et al, in order to compare the endometrial thickness and histopathological results measured by transvaginal ultrasonography in premenopausal patients with abnormal uterine bleeding, it was observed that the mean age of women was 40 years and above, and they were in the premenopausal period [6]. Aker et al examined the endometrial results in women with abnormal uterine bleeding, and in their study involving 765 cases, it was observed that the mean age of women was 43.14±7.92 in the premenopausal group and 60.7±7.88 in the postmenopausal group [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cervical mucus was sampled as previously described [4]. The samples were obtained with the women in the lithotomy position prior other vaginal maneuvers.…”
Section: P R E P R I N Tmentioning
confidence: 99%
“…Secretory leukocyte protease inhibitor (SLPI) is a low molecular-weight secretory protein found in the alveolar face of the lung, intestinal mucosa, and mucosal surface of the reproductive system [4]. The antimicrobial, anti-inflammatory, and antiprotease functions of SLPI have been demonstrated and they provide antiprotease activity with several types of serine proteases, including neutrophil elastase, cathepsin G, and trypsin [5].…”
Section: Introductionmentioning
confidence: 99%